Effects of dietary ratio of n-6 to n-3 polyunsaturated fatty acids on immunoglobulins, cytokines, fatty acid composition, and performance of lactating sows and suckling piglets - Yao, Wei (BioMed Central, 2012)
This experiment was conducted to investigate the effects of dietary ratios of n-6:n-3 polyunsaturated fatty acids (PUFA) on the performance of lactating sows and their piglets. Thirty pregnant Landrace sows were assigned to one of three treatments from d 108 of gestation until weaning (26–29 d) and were fed diets containing different ratios of n-6:n-3 PUFA including 3:1, 9:1 and 13:1. The effects on sow and litter production traits were examined together with an assessment of sow body condition. No differences were detected among the treatments for the daily feed intake of sows or changes in sow weight and back-fat levels during lactation (P > 0.05). Litter size at d 14 and d 21 were tended to increase in 3:1 treatment compared with 9:1 and 13:1 treatments (P < 0.10). Litter weight gain (1.77 kg/d) from d 0 to d 14 was tended to increase in 9:1 groups compared with the other two treatments (P < 0.10). A significant difference was observed for the content of α -linolenic acid, total n-3 PUFA, and the ratio of n-6:n-3 PUFA in the colostrum, milk, and piglets plasma (P < 0.01). The effects of different ratios of n-6:n-3 PUFA in sow diets on colostrum, milk, and piglet plasma immunoglobulin concentrations are studied. No difference was observed among treatments in the concentrations of IgM, and IgA in colostrum (P > 0.05). A great significant difference for IgG concentration was observed among 3 group in colostrum. A great significant difference for IgA, and IgM (P < 0.01) concentrations in piglet plasma at d14 and a significant difference for IgG(P < 0.05) was observed at d14. Furthermore, at d 21 of lactation, piglet plasma IgG and IgA concentration were greater in 3:1 compared with 13:1 group (P < 0.01). In summary, the current study demonstrated that altering the ratio of n-6:n-3 PUFA in lactating sow diet had an effect on the immune component including immunoglobulin and cytokines, and it tended to increase the litter average daily gain and improve the immune status of piglets when dietary ratio of n-6:n-3 PUFA was 9:1.